Effects of ball type and maturity status on U10 tennis players competition load - Rodríguez-Campos, Manrique; Piquer-Piquer, Ana; Giménez-Egido, José María; Ramón-Llin, Jesús; Francisco Guzmán, José; Sánchez-Alcaraz, Bernardino; Vuckovic, Goran; Martínez-Gallego, Rafael (Frontiers in Psychology, 2026)
IntroductionThe use of modified equipment in youth tennis, such as low-compression balls, is widely recommended to optimize learning, participation, and long-term athlete development. However, little is known about the physical demands imposed by these adaptations in under-10 (U10) competitive players, particularly when considering biological maturation.MethodsThis study analyzed 72 simulated tournament matches involving 19 tennis players (10.17 ± 1.1 years; 14 boys, 5 girls). Each player competed under two conditions: green balls (25% lower compression) and standard balls. External load variables (active time, recoveries, and work-rest ratio) were recorded with WIMU Pro™ inertial devices, while covariates such as maturity offset (PHV), years of practice, physical activity level, jump height, and number of tournaments were considered. Bayesian repeated-measures ANOVA models were applied to assess differences.ResultsModel comparisons consistently provided anecdotal to moderate evidence in favor of the null hypothesis for ball type, suggesting that any differences in external load between green and standard balls are likely trivial and of limited practical relevance, with wide credible intervals reflecting substantial individual variability. Conversely, biological maturation (PHV) emerged as the strongest predictor of active time and work-rest ratio, with players closer to their PHV showing reduced active time. Moderate to strong Bayes factors, together with credible intervals excluding zero, indicate a robust and meaningful influence of biological maturation on match demands.DiscussionThese findings suggest that, in U10 tennis, low-compression balls provide a pedagogical advantage without increasing external load. Instead, biological maturation plays a decisive role in modulating match demands. Green balls represent a convenient and developmentally appropriate tool in U10 tennis, but coaches should therefore prioritize maturity-based individualization of training and guiding the transition to standard ball, rather than relying solely on chronological age.